Film and finance. An attempt at a statistical comparison of the attendance results and ratings of Polish films in the years 2012–2015 - Adamczak, Marcin; Orankiewicz, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article is an attempt to use essential statistical tools for analysis of market performance of films and its aes- thetical judgements made by film critics and fans. The authors describe differences between evaluations of films by professional and non-professional viewers, correlations between market performance and artistic merit and impact of level of public support for success and quality of movies. The material for analysis are Polish films in cinema distribution between 2012 and 2015.